Standardy społecznej odpowiedzialności małego biznesu. Analiza porównawcza firm polskich i brytyjskich - Lewicka-Strzałecka, Anna (Annales. Etyka w Życiu Gospodarczym, 2008)
The aim of this article is to discern the crux of SME sector social responsibility in developingcountries. An attempt is made to identify, empirically, the ethical standards subscribed to by small firmsin Poland and to compare them with the standards of small firms in the UK. The methodology ofempirical analysis of the ethical standards of Polish entrepreneurs running small businesses wasmodelled on Laura Spence’s research on the priorities, practices and ethics of small firms in the UK.This analysis has revealed certain similarities and significant differences in the way CSR is perceivedby Polish and British entrepreneurs. British entrepreneurs manifest a higher degree of awareness withregard to the issue of social responsibility and are more strongly motivated by their externalenvironment to take up social responsibility issues than Polish ones.